Practical challenges in the development of photoelectrochemical solar fuels production. Issue 3 (17th December 2019) - Spitler, Mark T.; Modestino, Miguel A.; Deutsch, Todd G.; Xiang, Chengxiang X.; Durrant, James R.; Esposito, Daniel V.; Haussener, Sophia; Maldonado, Stephen; Sharp, Ian D.; Parkinson, Bruce A.; Ginley, David S.; Houle, Frances A.; et al.
Abstract : Analyses are made of the connectivity of PEC fuels market place, prototype and materials to create an efficient research focus. Abstract : This article addresses the challenges presented by photoelectrochemical solar fuels technology in a discussion that begins with a functioning device and proceeds to the more fundamental science of its component parts. In this flow of discussion issues are addressed that frame the discussion for the next, increasingly more fundamental topic. The analysis begins with a discussion of the need for an analytical facility for confirmation of reported efficiencies of solar fuels device prototypes and then progressively narrows its scope to prototype design, the discovery of novel materials and the design of durable interfacial structures for fuels evolution. Molecular hydrogen will be considered first as the target fuel since many of the challenges with hydrogen production are general and applicable to the more complex CO2 reduction, which will be treated as a supplementary subject.